Effects of COVID-19 on Blood Culture Contamination at a Tertiary Care Academic Medical Center - Brianna Sacchetti; Justin Travis; Lisa L. Steed; Ginny Webb (Microbiology Spectrum, 2022)
ABSTRACT The COVID-19 pandemic has changed health care, from increased needs of personal protective equipment (PPE) to overloaded staff and influxes of patients. Blood cultures are frequently used to detect bloodstream infections in critically ill patients, but it is unknown whether the COVID-19 pandemic has had an impact on blood culture contamination rates. A total of 88,332 blood cultures taken over a 33-month period were analyzed to compare blood culture contamination rates before the COVID-19 pandemic to rates during the pandemic. A significant increase in the average number of monthly nurse-drawn and peripherally collected cultures occurred after the start of the pandemic, but there was a decrease in the average number of phlebotomy cultures. A significant increase in contamination rates (P < 0.001) was found in all nonemergency hospital departments during the COVID-19 pandemic, increasing from 2.1% to 2.5%. Increased rates during the COVID-19 pandemic were also found for nursing staff (2.0% to 2.4%) and both peripheral (2.1% to 2.5%) and indwelling line draws (1.1% to 1.7). The number of cultures drawn monthly increased in acute adult departments and both adult and pediatric emergency departments. Blood culture contamination rates in adult acute, adult emergency, and pediatric intensive care units increased after the start of the pandemic by 23%, 75%, and 59%, respectively. A positive correlation was found between blood culture contamination rates and COVID-19 incidence rates. Additional periodic staff training on proper blood collection technique and awareness of the workload of health care workers are recommended to decrease contamination rates during the COVID-19 pandemic. IMPORTANCE Understanding factors that contribute to blood culture contamination is important in order to take steps to limit contamination events. Here, we examine the effect the COVID-19 pandemic has had on blood culture contamination rates and specifically detail the effects based on the staff, draw types, and unit types. The conclusions provided here can be used as hospitals and laboratories navigate the COVID-19 pandemic or other times of high patient volume.